Structural and electrochemical studies of a new Tavorite composition: LiVPO4OH. Issue 28 (1st July 2016) - Boivin, Edouard; Chotard, Jean-Noël; Ménétrier, Michel; Bourgeois, Lydie; Bamine, Tahya; Carlier, Dany; Fauth, François; Suard, Emmanuelle; Masquelier, Christian; Croguennec, Laurence
Abstract : A vanadium based hydroxy-phosphate of the Tavorite-type structure LiVPO4 OH was obtained for the first time, by a hydrothermal route. Li + and H + are extracted from the structure at the same equilibrium potential. Abstract : Polyanionic materials attract strong interest in the field of Li-ion battery research thanks to the wide range of compositions, structures and electrochemical properties they offer. Tavorite-type compositions offer a very rich crystal chemistry, among which LiVPO4 F has the highest theoretical energy density ( i.e. 655 W h kg −1 ). A new Tavorite-type LiVPO4 OH composition was synthesized by a hydrothermal route from three different vanadium-containing precursors. The crystal structure of this new phase was fully determined thanks to synchrotron X-ray and neutron diffraction. 1 H, 7 Li, and 31 P magic angle spinning nuclear magnetic resonance spectroscopy as well as diffuse reflectance infra-red spectroscopy were performed in order to support further the nature of the phases formed. Galvanostatic intermittent titration technique experiments in lithium batteries and ex situ X-ray diffraction analyses revealed that during oxidation the concomitant extraction of Li + and H + occurs at the same equilibrium potential (3.95 V vs. Li + /Li) and leads to the formation of the Tavorite phase VPO4 O at the end of the charge. LiVPO4 OH is also electrochemically active in the low voltage region, upon Li + insertion. The reversible insertion/extraction of lithium at 1.35 V vs. Li + /Li leads to the formation of Li2 VPO4 OH at the end of discharge.